Nanoparticle enhanced MRI can monitor macrophage response to CD47 mAb immunotherapy in osteosarcoma - Mohanty, Suchismita; Yerneni, Ketan; Theruvath, Johanna Lena; Graef, Claus Moritz; Nejadnik, Hossein; Lenkov, Olga; Pisani, Laura; Rosenberg, Jarrett; Mitra, Siddhartha; Cordero, Alejandro Sweet; Cheshier, Samuel; Daldrup-Link, Heike E. (Cell death & disease, 2019)
CD47 monoclonal antibodies (mAbs) activate tumor-associated macrophages (TAMs) in sarcomas to phagocytose and eliminate cancer cells. Though CD47 mAbs have entered clinical trials, diagnostic tests for monitoring therapy response in vivo are currently lacking. Ferumoxytol is an FDA-approved iron supplement which can be used “off label” as a contrast agent: the nanoparticle-based drug is phagocytosed by TAM and can be detected with magnetic resonance imaging (MRI). We evaluated if ferumoxytol-enhanced MRI can monitor TAM response to CD47 mAb therapy in osteosarcomas. Forty-eight osteosarcoma-bearing mice were treated with CD47 mAb or control IgG and underwent pre- and post-treatment ferumoxytol-MRI scans. Tumor enhancement, quantified as T2 relaxation times, was compared with the quantity of TAMs as determined by immunofluorescence microscopy and flow cytometry. Quantitative data were compared between experimental groups using exact two-sided Wilcoxon rank-sum tests. Compared to IgG-treated controls, CD47 mAb-treated tumors demonstrated significantly shortened T2 relaxation times on ferumoxytol-MRI scans ( p < 0.01) and significantly increased F4/80+CD80+ M1 macrophages on histopathology ( p < 0.01). CD47 mAb-treated F4/80+ macrophages demonstrated significantly augmented phagocytosis of ferumoxytol nanoparticles ( p < 0.01). Thus, we conclude that ferumoxytol-MRI can detect TAM response to CD47 mAb in mouse models of osteosarcoma. The ferumoxytol-MRI imaging test could be immediately applied to monitor CD47 mAb therapies in clinical trials.